How to read your fortune in a teacup : the ancient art of tea-leaf reading - Struthers, Jane (New York, NY Godsfield, an imprint of Octopus Publishing Group Ltd, 2024)
In this book, you'll find step-by-step instructions for interpreting the magic of tea leaves, tips for getting started, and useful hints to remember during readings. An illustrated directory to the meaning of 300 shapes and symbols, divided into six useful categories, will provide you with instant answers for questions about romance, travel, work, money, health, family and friends.
A short history of tea leaf reading -- The right tea things -- The Tasseomancy Ritual -- Reading the leaves -- Reading for every purpose -- Tea leaf directory.
Includes index.
115007
Keywords: Fortune-telling by tea leaves